SPIRITUAL UNITY OF LANGUAGE AND NATION - Poliuga, L. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article on the basis of opinions I.Franko there is an attempt to light up main factors – languages, cultures, intellect, - that are instrumental in claim of national spirituality and patriotism.